2021
DOI: 10.1038/s41598-021-94068-w
|View full text |Cite
|
Sign up to set email alerts
|

The first draft genome of feather grasses using SMRT sequencing and its implications in molecular studies of Stipa

Abstract: The Eurasian plant Stipa capillata is the most widespread species within feather grasses. Many taxa of the genus are dominants in steppe plant communities and can be used for their classification and in studies related to climate change. Moreover, some species are of economic importance mainly as fodder plants and can be used for soil remediation processes. Although large-scale molecular data has begun to appear, there is still no complete or draft genome for any Stipa species. Thus, here we present a single-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 125 publications
0
14
0
Order By: Relevance
“…However, it’s noteworthy that only 19 branches garnered support levels exceeding 50% ( Krawczyk et al., 2017 ). Similarly, Baiakhmetov constructed phylogenetic relationships for 14 Stipa species using nucleolar organizing regions (NORs), and their findings also indicated relatively low support in the resulting tree ( Baiakhmetov et al., 2021b ). It appears that there is a paradox in Stipa genus phylogenetic research.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, it’s noteworthy that only 19 branches garnered support levels exceeding 50% ( Krawczyk et al., 2017 ). Similarly, Baiakhmetov constructed phylogenetic relationships for 14 Stipa species using nucleolar organizing regions (NORs), and their findings also indicated relatively low support in the resulting tree ( Baiakhmetov et al., 2021b ). It appears that there is a paradox in Stipa genus phylogenetic research.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Baiakhmetov employed a genome-wide approach to obtain thousands of SNP genotypes for a phylogenetic analysis of a population comprising five Stipa species. The results indicated that fewer than half of the branches could be supported with a value of ≥0.8 ( Baiakhmetov et al., 2021b ). In our study, the high-confidence phylogenetic trees of Stipa were obtained from dozens and thousands of protein-coding genes, with almost 100% support for all branches ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations